Targeting severe symptoms of early 2023-new outbreak of COVID-19 by classical drug dexamethasone: a potential fatality reducing agent - Dongsheng Liu; Aamir Saeed; Sidra Majaz; Bashrat Ahmad; Ashfaq Ahmad; Yingqiu Xie (Springer Science and Business Media LLC, 2023)
binding analysis for five strains (Omicron, BJ.
Keywords: Outbreak; Case fatality rate; Dexamethasone; Coronavirus disease 2019 (COVID-19); Drug; Medicine; Virology; Pandemic; 2019-20 coronavirus outbreak; Environmental health; Intensive care medicine; Pharmacology; Internal medicine; Infectious disease (medical specialty); Disease; Population; type of access: open access